Implementasi Pelaksanaan Ketentuan Pasal 35 UU No.46 Tahun 2009 Tentang Pengadilan Tindak Pidana Korupsi Bertentangan Dengan Harapan Asas Peradilan Cepat, Sederhana Dan Biaya Ringan Terhadap Peradilan Tindak Pidana Korupsi Di Tingkat Kabupaten/Kota - Handrawan, Handrawan; Hasjad, Hasjad; Ustien, Dewi Oktoviana; Arpin, Syaiful (Universitas Batanghari Jambi, 2022)
Abstract :The focus of the study in this research is the implementation of the provisions of Article 35 of Law No. 46 of 2009 concerning Corruption Courts Contrary to the Expectations of Fast, Simple and Low Cost Judicial Principles for Corruption Courts at the Regency/City Level. This study aims to examine and analyze the subject matter, namely analyzing the problems of implementing the provisions of Article 35 of Law Number 46 Year 2009 concerning the court of corruption at the district/city level. To analyze the policy concept so that the judicial process for corruption at the district/city level can reflect the expectations of the principles of simple, fast and low-cost justice. To discuss these problems, the type of research used by the author is that this research is structured as